Impact of post - tsunami rehabilitation activities on selective fishing in the Northern coast of Jaffna peninsula - Kugathas, S.; Sivatharshan, Y.; Sivashanthini, K. (Proceedings of the International Forestry and Environment Symposium, 2006)
A questionnaire based survey was eonducted in May 2006, among the Tsunami affected fishermen of' Northern Jaffna peninsula, in order to assess the fishing effort after Tsunami rehabilitation activities. 4337 families along the coast from Valvettithurai to Kaddaikadu were included in to the survey and they were divided in to 72 sites according to their respective donor agencies. 16 Non governmental organizations were identified as donor agencies for permanent housing schemes, out of which 6 agencies directly donated fishing gears and boats. The types and numbers offishing gears and boats used before and after tsunami were recorded. Results indicate that all the traditional canoes have been replaced by fiber reinforced boats and the number of boats showed 12% increase after tsunami. Before tsunami, there were diverse types of fishing gears with wide range of mesh size. But post tsunami rehabil itation aids provided on Iy the gi II nets of2 different mesh sizes, one for fish and the other for skates. Although large numbers of boats have been given, most of them are not in use because of the prevailing unrest situation in this region. Therefore fishing effort due to the increased number of boats is immaterial. But reduced diversity of fishing gear will have major impact on stock. Since fishing is restricted in to a narrow belt along the coast repeated use of skate gill net by most of the fishermen will lead to an over exploitation of skate species. Similarly, selective fishing by gill net will deplete coastal fish species. Therefore donor agencies should focus on remedial actions in order to diversify the fishing gears in type and in mesh size.